Zoonotic importance of ecto- and endoparasites in rodents in Malaysia: a review - Firdaus, Mohd-Qawiem; Md Isa, Nur-Mahiza; Ahmad, Nur Indah; Abd Rahaman, Yasmin; Saulol Hamid, Nur-Fazila (Korean Society of Veterinary Science, 2024)
Importance Rodents, particularly those inhabiting urban areas, are sources of infections that cause major human diseases. The number of recorded zoonotic infections has increased in recent decades, exacerbating public concerns. Zoonotic diseases in humans, such as capillariasis, hymenolepiasis, and toxoplasmosis, are life-threatening in severe cases, particularly in immunocompromised individuals. A thorough understanding of pathogens, particularly the parasites infecting rodents, is critical for predicting future zoonotic disease outbreaks and developing effective mitigation strategies. This review summarizes the information on parasites in rodents inhabiting Malaysia to identify the knowledge gaps that could serve as a foundation for future research. Observations Thirty-eight previous parasite studies in rodents conducted in Malaysia were reviewed, and 44 ectoparasites species and 58 endoparasites species across 19 rodent species were revealed. Six ectoparasite and eight endoparasite species were identified as zoonotic among these parasites. Morphological identification of parasite species typically succeeded only at the genus level because of their identical morphological characteristics. However, these studies used a molecular approach to identify parasites at the species level using species-specific primers. The pathological findings of various organs of infected rodents were also summarized, including gross and histological lesions exhibited by parasites. Conclusions and Relevance This review highlights the list of parasites infecting rodents in Malaysia, provides information on the molecular and pathological findings from previous studies, and identifies some of the limitations and knowledge gaps that suggest future research to address the issues, including the paucity of information on blood parasites, molecular, and histopathological studies of parasites in rodents.